Pengaruh Pergaulan Teman Sebaya Terhadap Pembentukan Karakter Santri di Pondok Pesantren Assunniyyah - sasa amelia putri (Universitas Al-Falah As-Sunniyah Kencong Jember, 2026)
The purpose of this study is to understand the impact of the sebaya theme on the development of the santri character in Pondok Pesantren Assunniyyah. Pergaulan teman sebaya is one of the social factors that has a significant impact on the development of remaja, especially in the context of pesantren-based education. The method of research that is used is quantitative with a korelasional approach. This research sample consists of 60 santri that are collected in a purposeful manner. The instrument used is a Likert scale angket. The results of the data analysis indicate that there is a significant difference between the sebaya theme's pergaulan and the santri character's development (nilai signifikansi p < 0.05). Some of these characteristics are discipline, religiosity, tanggung jawab, and kemandirian. This highlights the importance of social environment education in character education at the pesantren.